FREEDOM OF SPEECH AND SCIENTIFIC ACCURACY: A CRITICAL ANALYSIS OF LEGAL CHALLENGES IN SCIENCE COMMUNICATION - Sharma, Pradeep Kumar; Mishra, Sangharsh; Sandeep Kumar Suman; Arvind (ShodhKosh: Journal of Visual and Performing Arts, 2024)
As science communication becomes increasingly popularized through diverse media channels, including social media, podcasts, documentaries, and public lectures, legal systems are confronted with unprecedented challenges in defining boundaries of responsibility, accountability, and potential liability. In this context this article explores the emerging legal frameworks governing the dissemination of scientific knowledge, analyzing the intricate balance between scientific integrity, public understanding, and regulatory oversight. The research paper critically examines several key dimensions, like Liability and Misinformation regarding, investigating legal mechanisms to address scientific misinformation, exploring potential legal consequences for intentional or negligent misrepresentation of scientific findings, analyzing the tension between freedom of speech and scientific accuracy